The Pharm.D. in Pakistan: A Curricular Innovation in Health Systems Instruction - Dr Shaukat Khalid, Dean; Dr Fazal, The Executive Officer (University of Minnesota Libraries Publishing, 2011)
This is the first article of its type to describe the advances taking place in clinical pharmacy education in Pakistan. The Pharmacy Council of Pakistan has developed a five-year Pharm.D program to replace the four-year B.Pharm degree. Completing clinical pharmacy clerkships is a prerequisite for receiving the Pharm.D degree. To meet this requirement, Ziauddin College of Pharmacy has developed a specialized clerkship program for its 4th and 5th year students. The College is fortunate to be linked with well developed tertiary care hospitals at three prime locations in the in the metropolitan city of Karachi, which provides opportunity for the students to gain exposure to real life situations and work with patients. The article presents an account of the efforts taken for development of the clinical pharmacy clerkship program, the problems encountered during its development, and the main outcomes of a clerkship program.